Pelatihan dan Pendampingan Blended Learning Berbasis Moodle dalam Pembelajaran Matematika di SMP Negeri 1 Magelang dan SMP Negeri 2 Magelang - Syita Fatih 'Adna; Aprilia Nurul Chasanah; Nur Baiti Nasution (Universitas Tidar, 2023)
Entering the new normal era, Mathematics learning is carried out using blended learning. However, in its implementation so far it has not run optimally. Discussions held online were not well facilitated, materials were only sent via whatsapp groups, and documentation was not good. Mathematics learning should be presented in an attractive manner by utilizing learning technology in accordance with the times. One of the platforms that can be used is the Moodle platform, which can be implemented simultaneously for face-to-face learning and online learning. Through Moodle, teachers can provide materials, videos, assignments, and quizzes that students can access anytime and anywhere, and create discussion forums with their students. Students who find it difficult to learn mathematics can ask the forum according to the topic of discussion. Thus, it is necessary to hold service activities in the form of training and mentoring of Moodle-based blended learning in learning mathematics at SMP Negeri 1 Magelang and SMP Negeri 2 Magelang. The purpose of this service activity is to provide training and mentoring for Moodle-based blended learning in mathematics learning at SMP Negeri 1 Magelang and SMP Negeri 2 Magelang as an innovation in learning mathematics.The target of this service is to transfer the science and technology of junior high school learning innovations to teachers at SMP Negeri 1 Magelang and SMP Negeri 2 Magelang in the form of training and mentoring, in the form of: (1) introduction to the Moodle platform and its features, (2) training in making teaching materials, assignments, quizzes, and videos using the Moodle platform, and (3) mentoring the use of Moodle in junior high school learning. The methods used in this service are lecture, question and answer, and practice methods. Service activities are carried out for 4 months in several stages, namely planning, implementing, evaluating, and reporting the results of service activities. The result of community service activities is an increase in skills using the Moodle platform for mathematics teachers at SMP Negeri 1 Magelang and SMP Negeri 2 Magelang in blended learning-based Mathematics learning.